Analysis Of The Relationship Between Factors Of Providing Complementary Foods, Exclusive Breastfeeding, And Immunization With Stunting - Yuliawati, Yuliawati; Putri, Reza Resinta; Widiyanti, Septi; Sadiman, Sadiman (JKM (Jurnal Kebidanan Malahayati), 2024)
Latar Belakang: Stunting merupakan kondisi tinggi badan anak lebih pendek dari standar usianya. Prevalensi stunting di Kota Metro tahun 2021 sebesar 7,29% dan meningkat menjadi 10,4% pada tahun 2022. Di Puskesmas Yosomulyo, prevalensi stunting mencapai 11% pada tahun 2021 dan tetap sama pada tahun 2022. Penelitian ini bertujuan untuk mengetahui hubungan antara pemberian MP-ASI, ASI Eksklusif, dan imunisasi lengkap dengan stunting.Metode: Penelitian ini menggunakan desain case-control dengan total sampel 66 responden, terdiri dari 33 kasus stunting dan 33 kontrol. Pengambilan sampel dilakukan dengan accidental sampling, dan data dikumpulkan melalui wawancara dan dokumentasi. Analisis data menggunakan uji Chi-Square.Hasil: Hasil penelitian menunjukkan ada hubungan signifikan antara MP-ASI dengan nilai p=0,047), ASI Eksklusif dengan nilai p=0,013, dan imunisasi dengan nilai p=0,023 dengan kejadian stunting. Simpulan: ada hubungan antara pemberian MP-ASI tidak sesuai, ASI Eksklusif, dan imunisasi tidak lengkap dengan stunting.Saran: Health workers, especially midwives, can increase the role of mothers by increasing the provision of breast milk, complementary feeding, and complete immunization according to age. Kata kunci: ASI Eksklusif, Imunisasi, Makanan Pendamping ASI, dan Stunting. ABSTRACT Background: Stunting is a condition where a child's height is shorter than the standard for their age. The prevalence of stunting in Metro City in 2021 was 7.29% and increased to 10.4% in 2022. At the Yosomulyo Health Center, the prevalence of stunting reached 11% in 2021 and remained the same in 2022. This study aims to determine the relationship between the provision of complementary feeding, exclusive breastfeeding, and complete immunization with stunting. This study used a case-control design with a total sample of 66 respondents, consisting of 33 stunting cases and 33 controls. Sampling was carried out by accidental sampling, and data were collected through interviews and documentation.Method: This study used a case-control design with a total sample of 66 respondents, consisting of 33 stunting cases and 33 controls. Sampling was done by accidental sampling.  Data analysis used the Chi-Square test.Data analysis used the Chi-Square test.Results: The results showed a significant relationship between complementary feeding with a p value = 0.047), exclusive breastfeeding with a p value = 0.013, and immunization with a p value = 0.023 with the incidence of stunting.Conclusion: There is a relationship between the provision of inappropriate complementary feeding, exclusive breastfeeding, and incomplete immunization with stunting Keywords: Exclusive Breastfeeding, Immunization, Complementary Foods, and Stunting.